Steen Johansen 1908-1987 - Høirup, Henning (Grundtvig-studier, 1987)
Steen Johansen 1908-1987 in memorian By Henning Høirup. The first article in Grundtvig-Studier 1987 is an obituary on Steen Johansen, who died in 1987. He was a founding member of the Grundtvig Society. His main work is Bibliografi over N. F. S. Grundtvigs Skrifter I-IV, 1948-1954. He was a leading collaborator on the registrant listing Grundtvig’s unpublished papers, just as he was a prominent contributor to Grundtvig Studier. The obituarist is Bishop Henning Høirup D.D.